2021
DOI: 10.1177/0967391121998823
|View full text |Cite
|
Sign up to set email alerts
|

Tribological response of polycarbonate and acrylonitrile butadiene styrene blends containing fixed amounts of Kevlar fibre and molybdenum disulphide with varying quantities of betel nut powder

Abstract: In this study, the composites with incorporation betel nut powder at three levels (10, 18 and 25%) in Polycarbonate (PC) and Acrylonitrile Butadiene Styrene (ABS) matrices having Kevlar Fibres (KF) and Molybdenum Disulphide (MoS2) nano particles in fixed amounts are looked into for their tribological characteristics. The effect of hardness, surface roughness and density was evaluated. FTIR and X-ray diffraction (XRD) studies have been carried out to identify the phases. The effects of load on the slide wear lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…One is to improve the characteristics of the lubricating medium [3,4], while the other is to develop e cient inorganic sliding pairs as alternatives to the conventional metal-tometal friction pairs. Over the past two decades, extensive research has been conducted on the tribological properties and processes of polymer composites, particularly ber-reinforced composites [5][6][7][8]. In recent years, it has been found that the tribological performance of ber-reinforced polymer composites can be further enhanced by incorporating sub-and nanoparticles, such as TiO 2 , ZnS, SiO 2 , B 4 C, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One is to improve the characteristics of the lubricating medium [3,4], while the other is to develop e cient inorganic sliding pairs as alternatives to the conventional metal-tometal friction pairs. Over the past two decades, extensive research has been conducted on the tribological properties and processes of polymer composites, particularly ber-reinforced composites [5][6][7][8]. In recent years, it has been found that the tribological performance of ber-reinforced polymer composites can be further enhanced by incorporating sub-and nanoparticles, such as TiO 2 , ZnS, SiO 2 , B 4 C, etc.…”
Section: Introductionmentioning
confidence: 99%